The structure and properties of water - Eisenberg, David S.; Kauzmann, Walter, 1916-; Oxford eBooks (Oxford : Oxford University Press, 2005)
The authors have correlated many experimental observations and theoretical discussions from the scientific literature on water. Topics covered include the water molecule and forces between water molecules, the thermodynamic properties of steam, the structures of the ices, hydrogen bonding in ice and water and much more.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Water; Electronic books